Os territórios da agricultura familiar e patronal na área de proteção ambiental (APA) do Ibirapuitã/RS: divergências e convergências na lógica de reprodução social - Losekann, Marilse Beatriz (2018)
This work presents a study about the territories and territorialities of the farmers and family members who live in the Environmental Protection Area (APA) do Ibirapuitã, Unit of Conservation of Sustainable Use of the Pampa Biome, Rio Grande do Sul. It aims to understand which strategies of social reproduction are employed as well as the adaptations to the standards of the Conservation Unit. The study is based on qualitative research and among the instruments and techniques were used bibliographic and documentary research, field work, semi-structured interviews, systematic observation, use of photographs and finally the analysis and discussion of the information. The results show that in the territory of the Conservation Unit, APA do Ibirapuitã, extensive livestock management still prevails over the natural field, thus maintaining the local cultural and environmental characteristics of the Pampa Biome, and maintaining the historical coexistence of patronal agriculture and family. Some traditional practices such as decommissioning are presented as conflicting with the legal norms of the CU. Among the main strategies of social reproduction are, both among employers and among their families: self-organization such as the Associations of Producers of the Rincão do 28 and Rincão do Batista, the Quilombola Community Rincão da Chirca, as well as forms of non-institutionalized cooperation such as the joint sale of animals by neighbors which maintain similar productive characteristics; lease or partnership; the introduction of the discourse and sustainable practices that have contributed to the conservation of the APA; and the insertion of women in the decision-making and daily activities of the champions, a strategy that is used in the family territories. CONAPA, the Administrative Council of the APA, is configured as a dialogical instrument between the individuals and institutions that make up the territory of the Conservation Unit, it is necessary that there is an increase in the representativeness of the residents of the APA, since this is only possible to guarantee that there is correspondence of the demands of the community involved with the protected space, as well as, it is essential that the meetings occur regularly. For these problems to be overcome, it is critical that the structural demands of the APA be addressed, such as the allocation of more funds and environmental analysts to APA.